Circular economy business model innovation: Sectorial patterns within manufacturing companies. (1st March 2021) - Pieroni, Marina P.P.; McAloone, Tim C.; Pigosso, Daniela C.A.
Abstract: The market penetration of business models for circular economy is limited in most manufacturing sectors due to shortcomings in capabilities of companies to execute circular economy business model innovation. Available approaches are still generic and provide limited help for contextualised solutions within sectorial challenges. This paper introduces sectorial business model patterns to support manufacturing companies to reduce complexity and uncertainty within circular economy business model innovation. Based on a multidimensional scaling analysis of more than 180 cases of companies that implemented circular economy business models, a number of sectorial patterns were consolidated for six selected sectors. The patterns prescribe a combination of business models configuration options and architectures for tackling specific sources of structural waste. Testing with manufacturing companies revealed the potential of the sectorial patterns to support: (1) visualisation of viability and feasibility of circular economy business models, which strengthens motivation and arguments for their implementation; and (2) reduction of uncertainties and complexity, which facilitates the exploration of business models with higher impact for circular economy. In addition to providing insights about pattern variations across sectors, a procedure for the development of business model patterns is put forward, which can be expanded to other sectors and/or emerging cases.